Los equinodermos (Echinodermata) de El Salvador - Barraza, José Enrique (2005)
The echinoderms (Echinodermata) from El Salvador. A list of echinoderms from El Salvador (tropical eastern Pacific) is presented. The results were obtained from field surveys (between the years 2000 and 2004), the scarce literature sources, and Internet information. A total of 37 species and six genera are reported. The most abundant echinoderms in rocky shores were: Phataria unifascialis, Echinometra vanbrunti, Holothuria kefersteini, as well as Astropecten armatus in soft bottoms. Rev. Biol. Trop. 53(Suppl. 3): 139-146. Epub 2006 Jan 30.